Improving Student Learning Outcomes in Islamic Education Learning Using Artificial Intelligence Assisted Learning Media at SD Negeri 5 Padang Sibusuk - Apriyalianti (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using artificial intelligence assisted learning media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that artificial intelligence assisted learning media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.19%, the first cycle 72.87% and in the second cycle increasing to 89.52%. Thus, the use of artificial intelligence assisted learning media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.